The role of Stress Inducible Protein 1 (STI1) in the regulation of actin dynamics - Beckley, Samantha Joy (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Stress-inducible protein 1 (STI1) otherwise known as Hop (Hsp70/Hsp90 organising protein) is a highly conserved abundant co-chaperone of the Hsp70 and Hsp90 chaperones. STI1 acts as an adapter protein, where it regulates the transfer of protein substrates from Hsp70 to Hsp90 during the assembly of a number of chaperone-client protein complexes. The role of STI1 associating independently with non-chaperone proteins has become increasingly prominent. Recent data from colocalisation and co-sedimentation analyses in our laboratory suggested a direct interaction between STI1 and the cytoskeletal protein, actin. However, there was a lack of information on the motifs which mediated this interaction, as well as the exact role of STI1 in the regulation of cytoskeletal dynamics. Two putative actin binding motifs, DAYKKK (within the TPR2A domain) and a polyproline region (after the DP1 domain), were identified in mammalian STI1. Our data from in vitro interaction studies including surface plasmon resonance and high speed co-sedimentation assays suggested that both TPR1 and TPR2AB were required for the STI1-actin interaction, and peptides corresponding to either the DAYKKK or the polyproline motif, alone or in combination, could not block the STI1-actin interaction. Full length mSTI1 was shown to have ATPase activity and when combined with actin an increase in ATPase activity was seen. Ex vivo studies using STI1 knockdown shRNA HEK293T cells and non-targeting control shRNA HEK293T cells showed a change of F-actin morphology as well as reduction in levels of actin-binding proteins profilin, cofilin and tubulin in the STI1 knockdown cells. These data extend our understanding of the role of STI1 in regulating actin dynamics and may have implications for cell migration.
Keywords: Heat shock proteins; Molecular chaperones; Actin; Microfilament proteins; Cell migration; Adenosine triphosphatase; Metastasis